2005
DOI: 10.1681/asn.2004121130
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Clinical Implications of Development of Donor-Specific and Non–Donor-Specific HLA Antibodies after Kidney Transplantation

Abstract: The involvement of immunologic and nonimmunologic events in long-term kidney allograft failure is difficult to assess. The development of HLA antibodies after transplantation is the witness of ongoing reactivity against the transplant, and several studies have suggested that the presence of HLA antibodies correlates with poor graft survival. However, they have not discriminated between donor-specific (DS) and non-specific (NDS) antibodies. A total of 1229 recipients of a kidney graft, transplanted between 1972… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
179
2
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 274 publications
(206 citation statements)
references
References 20 publications
18
179
2
7
Order By: Relevance
“…Whereas the robust antibody response in early AMR results in complement-mediated lytic injury of the endothelium and rapidly progressive allograft dysfunction allowing an early diagnosis, the smoldering generation of de novo DSA observed in late AMR results in nonlytic complementmediated injury, partial accommodation, and slow allograft dysfunction. [25][26][27][28] Whether the differences in the nature of the Table 3. CLINICAL RESEARCH www.jasn.org immune response influence the response to therapy in these entities has yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the robust antibody response in early AMR results in complement-mediated lytic injury of the endothelium and rapidly progressive allograft dysfunction allowing an early diagnosis, the smoldering generation of de novo DSA observed in late AMR results in nonlytic complementmediated injury, partial accommodation, and slow allograft dysfunction. [25][26][27][28] Whether the differences in the nature of the Table 3. CLINICAL RESEARCH www.jasn.org immune response influence the response to therapy in these entities has yet to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that circulating anti-HLA class I or II antibodies, either donor reactive (35,36) or de novo, non-donor reactive (36,37), are found in a substantial fraction of renal allograft recipients, and these are associated with later graft loss. Among 2278 recipients who were followed prospectively, graft failure 1 yr later was greater in those with alloantibodies than in those without (8.6 versus 3.0%; P Ͻ 0.0001).…”
Section: Chronic Humoral Rejectionmentioning
confidence: 99%
“…Among nine patients with antibodies with biopsies, six had C4d staining, whereas in 11 patients without antibodies, none had C4d staining (23). In 1229 patients who were investigated 1 to 5 yr after transplantation, 5.5% had DSA, 11.3% had non-DSA, and 83% had no HLA antibodies (24). The presence of either DSA or non-DSA correlated with lower graft survival, poor transplantation function, and proteinuria.…”
Section: Dsamentioning
confidence: 97%